THE PERSPECTIVES OF THE DIGITAL MARKETING - PhD. Porsayev G (International Journal of Human Computing Studies, 2020)
The article highlights the perspectives of digital marketing and its application in the economy. In particular, author gives examples of real world applications of digital marketing and the mainstream research on studying the consumer behavior